Peculiarities of Precocious Puberty in Boys and Girls With McCune-Albright Syndrome - Corica, Domenico; Aversa, Tommaso; Pepe, Giorgia; De Luca, Filippo; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2018)
McCune-Albright Syndrome (MAS; OMIM # 174800) is a rare, sporadic disease caused by a postzygotic, activating mutation in the guanine-nucleotide binding protein α-subunit (GNAS1) gene. MAS is characterized by the clinical triad of polyostotic fibrous dysplasia of bone, café-au-lait skin pigmentation and peripheral precocious puberty. However, clinical presentation is highly variable depending on mosaic tissue distribution of mutant-bearing cells. Precocious puberty is the most common endocrine manifestation of MAS and is often the presenting, and sometimes the only, clinical sign of MAS. Due to the very low prevalence of MAS, data on course of precocious puberty, effectiveness of treatments and gonadal function during post-pubertal period are lacking. Our knowledge on this issue derives essentially from case reports and small cohorts of patients. The aim of this review is to report all available literature data on clinical aspects, therapeutic management and outcomes of precocious puberty in children with MAS. A systematic research was carried out through MEDLINE via PubMed, EMBASE, Web of Science, Semantic Scholar, Cochrane Library.